Effect of pgf2 Î± administration before uterine flushing on embryo recovery rate in superovulated cows and heifers - Valencia, Javier; Flores, Mario; Sánchez Aldana, Arturo; Anta, Everardo (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Donor cows usually receive an injection of PGF2 alpha or analogues (PG) after embryo recovery to avoid occurrence of pregnancy. Due to its capacity to stimulate uterine contractions it has been suggested that an increase in embryo recovery could be obtained if the PG is injected before collection. The aim of this experiment was to evaluate, if the injection of PG 3 h before collection improves embryo recovery. A group of 334 donor cows and heifers (302 Holstein, 28 Brown Swiss and 4 Jersey), were superovulated with FSH-P, inseminated and assigned according to breed and parity to the following groups: (1) treatment group (114 heifers and 31 cows) were injected with 50 mg of PGF2 alpha, 3 hours before embryo collection and (2) control group (121 heifers and 38 cows) were injected with saline at the same time interval. Embryos were recovered non-surgically on days 6.5 to 7.5 following estrus. Number of corpora lutea, recovery rate of embryos and number of transferable embryos in each group were recorded. No differences (P>0.05) were found for any parameter between the treated and the control groups. The results show that the injection of PG 3 hours before embryo collection does not improve embryo recovery rate.